Development of Integrated Physics Teaching Materials Virtual Laboratory PhET Simulation on Student’s Critical Thinking Skills - Herlina, Herlina; Arsyad, Muhammad; Palloan, Pariabti (Jurnal Ilmiah Pendidikan Fisika, 2025)
The world of education plays an important role in improving the quality of human resources through quality learning activities, namely through the development of adequate teaching materials to provide clear direction related to the competencies to be achieved. This research is development research that aims to produce integrated physics teaching materials, such as Virtual Laboratory PhET Simulation, that are valid, practical, and able to improve students' critical thinking skills. The development model for integrated physics teaching materials, the Virtual Laboratory PhET Simulation, is a 4D learning model (Define, Design, Develop, and Disseminate). Based on the results of data analysis, the following conclusions were obtained: 1) integrated physics teaching materials Virtual Laboratory PhET Simulation are declared valid and suitable for use with an expert agreement index value of 0.72 for the aspect of content suitability, 0.67 for the aspect of the presentation, 0.73 for the aspect of language, and 0.68 for the aspect of graphics; 2) integrated physics teaching materials Virtual Laboratory PhET Simulation reviewed from the response of practitioners, namely physics subject teachers, are in the very good category; 3) The effectiveness of the integrated physics teaching material PhET Virtual Laboratory Simulation reviewed from students' critical thinking skills obtained an average N-Gain value of 0.44 and is in the moderate category. Students experience increased critical thinking skills in interpretation, analysis, inference, evaluation, and explanation. It can be interpreted that the integrated physics teaching materials that the Virtual Laboratory PhET Simulation developed effectively improve students’ critical thinking skills.